Spreading ideologies through tweets : examining extreme and moderate Muslims usage of Twitter - Salameh, Ahmad (2018)
Twitter enables groups with certain agendas to organize and distribute their ideologies. This research compares the different practices performed by the extreme and the moderate Muslims to build their networks and recruit more followers. We carry out our research in the context of religious communication on Twitter. The study contains two data sets of tweets written in the Arabic language; the first one is retrieved from certain accounts that are leaning to extremism or moderation based on the generated content by the account holders, and the second one is obtained through predefined keywords related to Islam. Collected tweets and retweets were analyzed through network analysis to understand users’ networking behavior, and to examine whether polarization exists. Regression analysis showed that negative sentiment in tweets has a significant positive impact on the retweeting quantity, while interestingly; positive sentiment was not statically significant to affect retweeting. Features of hashtags, URLs, tweet length, and the number of followers have a positive effect on retweeting, whereas the number of mentioned names has a significant negative effect on retweeting. Through network and centrality measures, we found that extreme and moderate users have higher frequency of interaction within their ideological group than with the ideologically-opposed users. We also suggest, based on our findings and related research, that extreme and moderate Muslims use provocation to introduce their partisan content to ideologically opposed users.